KopAL - An Orientation System For Patients With Dementia - Fudickar, Sebastian; Schnor, Bettina; Felber, Juliane; Neyer, Franz J; Lenz, Mathias; Stede, Manfred (Series Ambient Intelligence and Smart Environments, Volume 9: Behaviour Monitoring and Interpretation - BMI, 2011)
As a result of the aging societies in the western world, the impact of dementia, with its characteristics like disorientation and obliviousness is becoming a significant problem to an increasing amount of persons and the health system. To enable such dementia patients to regain a self determined life, we have developed a mobile orientation system called KopAL that assists dementia patients in every day problems, like remembering appointments, keeping track within their familiar surroundings as well as informing caretakers in critical situations, with a focus on minimal operational costs and a speech based human computer interface. While easy-to-use was one of KopALs requirements, the system itself uses and experiments with new technologies in the field of Mobile Ad Hoc Networks (MANETs), VoIP, and embedded systems. Further, KopAL is an interdisciplinary project. It is developed at Potsdam University within the Assisted Living Initiative of the Institute of Computer Science [3]. The working group Applied Computational Linguisics of Potsdam University cooperates to integrate speech generation and recognition on embedded systems. Psychologies from the University of Jena evaluate the project from the beginning: in helping to figure out the real user demands and a suited user-interface.